Key virulence genes associated with Streptococcus mutans biofilm formation: a systematic review - Fitri, Dinda Kurnia; Tuygunov, Nozimjon; Wan Harun, Wan Himratul Aznita; Purwasena, Isty Adhitya; Cahyanto, Arief; Zakaria, Myrna Nurlatifah (Frontiers in Oral Health, 2025)
IntroductionStreptococcus mutans is central to plaque-induced oral diseases due to its robust biofilm-forming ability. Understanding the genetic and regulatory basis of this process is critical for developing targeted anti-virulence strategies that preserve the balance of the oral microbiome. This systematic review aims to gather and evaluate existing evidence on the virulence genes associated with Streptococcus mutans biofilm formation.MethodsA comprehensive search of PubMed, Scopus, and Web of Science was conducted in accordance with PRISMA guidelines. Studies investigating the genetic and regulatory mechanisms of biofilm formation, as well as the effects of experimental treatments, were included, and the risk of bias was assessed using the QUIN tool.ResultsKey virulence genes were identified, including glucosyltransferases (gtfB, gtfC, gtfD), glucan-binding proteins (gbpB, gbpC), and two-component systems (vicRK, liaSR). These genes contribute to adhesion, extracellular polysaccharide synthesis, and environmental adaptation, processes critical for biofilm development. Various anti-virulence strategies, such as quorum sensing inhibitors and gene-targeted compounds, show promise in controlling biofilm formation without compromising bacterial viability, thereby preserving the homeostasis of the normal oral flora, which is essential for maintaining overall oral health.ConclusionWhile key virulence genes have been well characterized, further research is needed to clarify how their regulation is influenced by environmental conditions. Insights from this review may support the development of novel therapeutic approaches that reduce Streptococcus mutans pathogenicity while maintaining oral microbial balance.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024577977, PROSPERO CRD42024577977.